Synergies between radiotherapy and immunotherapy: a systematic review from mechanism to clinical application - Jiang, JingLong; Li, HouZe; Ma, QingCui; Liu, Jing; Ren, Fu; Song, YingQiu; Wang, TianLu; Li, KeYan; Li, Ning (Frontiers in Immunology, 2025)
The combination of radiation therapy (radiotherapy) with immunotherapy is changing the landscape of cancer treatment. Radiation damage tumor cell DNA through high-energy rays directly causes cell death or growth arrest; Immunotherapy works by boosting a patient’s own immune system’s ability to recognize and destroy cancer cells. The combination of the two not only enhances the local control of the tumor, but may also activate the systemic anti-tumor immune response, transforming the “cold” tumor into a “hot” tumor, thereby improving the survival rate and quality of life of patients. In recent years, this combined treatment approach has shown remarkable efficacy in a variety of cancers, especially non-small cell lung cancer and melanoma, among others. However, how to optimize radiation dose, timing and combination with immunotherapy drugs remains the focus of research. This paper first discusses the effect of radiotherapy on immune system, then analyzes the killing effect of radiotherapy and its mechanism, and finally discusses the latest progress and challenges of the combined application of radiotherapy and immunotherapy. Each section aims to provide clinicians and researchers with an in-depth understanding with a view to optimizing treatment strategies and improving outcomes for cancer patients.